The role of IL6 and ESR1 gene polymorphisms as immunological factors of pregnancy maintenance - Kucherenko, A.M.; Vorobiova, I.I.; Rudakova, N.V.; Livshits, L.A. (Вiopolymers and Cell, 2013)
Aim. The study is aimed at the evaluation of the association of IL6 gene -174G/C polymorphism and ESR1 gene -397C/T polymorphism with recurrent pregnancy loss (RPL) pathogenesis and at the investigation of the ESR1 gene -397C/T variant regulatory significance for the IL6 gene function. Methods. A case group of 75 women with RPL history and a control group of 106 unrelated healthy women, who have given birth to at least one child conceived in natural way, were genotyped by a PCR based restriction fragment length polymorphism assay. Results. There was no significant difference in IL6 -174G/C or ESR1 -397C/T genotype and allele frequencies between the case and control groups. Combined genotype distribution analysis showed significantly (p < 0.05) lower frequency of individuals homozygous for both IL6 -174G and ESR1 -397C alleles in case group (0.026) comparing to control (0.094). Conclusions. Genotype comprising IL6 -174G and ESR1 -397C alleles in homozygous state may be considered as a genetic marker of successful pregnancy maintenance during gestation early stages.